Assimilating Low‐Cost High‐Frequency Sensor Data in Watershed Water Quality Modeling: A Bayesian Approach. Issue 4 (24th April 2023) - Han, Feng; Hu, Zhaoping; Chen, Nengwang; Wang, Yao; Jiang, Jiping; Zheng, Yi
Abstract: Uncertainty reduction in watershed water quality (WWQ) modeling remains a major challenge. One important reason is the lack of sufficient available water quality observations because traditional laboratory analysis of water samples has high labor, financial and time costs. Low‐cost high‐frequency water quality data from in‐situ sensors provide an opportunity to solve this problem. However, long‐term sensing in complex natural environments usually suffers more significant errors. This study aimed to develop a novel method to utilize in‐situ sensor data in WWQ modeling, namely, the Bayesian calibration using multisource observations (BCMSO), which can simultaneously assimilate laboratory‐based observations and in‐situ sensor data. Both synthetic and real‐world cases of nitrate modeling were used to demonstrate the methodology, and the Soil and Water Assessment Tool was employed as the WWQ model. The results indicated that direct assimilation of sensor data using traditional Bayesian calibration generated obvious deviations in parameter inference and model simulation, which could consequently bias future predictions and affect management decision correctness. However, after proper treatment of errors in sensor data, the BCMSO method could extract meaningful information from sensor data and prevent negative impacts of errors. The modeling uncertainty was also greatly reduced. In the real‐world case, with 1 yr of subhourly electrical conductivity sensor data incorporated, the modeling uncertainty of nitrate concentration and management cost of controlling nitrate pollution were reduced by 70%. The BCMSO method provides a flexible framework to accommodate nonconventional observations in environmental modeling and can be easily extended to other modeling fields. Key Points: A novel method to utilize low‐cost high‐frequency in‐situ sensor data in watershed water quality modeling was developed With proper error treatment, the new method can extract meaningful information from in‐situ sensor data and improve modeling accuracy Assimilating 1 yr of subhourly EC sensor data reduced the modeling uncertainty and management cost by 70%